Contato dialetal: atitudes do falar Paraibano em São Paulo - Silva, Mikaylson Rocha da (2016)
This study aims to investigate the process of linguistic accommodation between varieties of Brazilian Portuguese of speakers from Paraíba living in São Paulo. We seek to understand how speakers, in dialect contact with other linguistic variety, assimilate new phonetic-phonological, lexical and discursive traits, as well as taking into account the study of linguistic accommodation, whether extralinguistic and linguistic factors play a determinant role as variables conditioners to linguistic convergence. During the research, some phonological phenomena will allow us to verify the effects of accommodation: the (non) palatalization of coronal / s / prior to the voiced and unvoiced dental plosives / t / and / d /. It will also be analyzed the stylistic, social and attitudinal variables of speakers to understand the incidence of the phenomenon studied. We believe that the attitudinal variable might influence to this studied phenomenon, and according to Fernández (1998), negative attitudes can slow the process of accommodation between dialects. Attitudes will be observed from the speeches of the speakers in the qualitative section of this work. The methodology that guides this study is descriptive explanatory and to account for the quantitative control of the variables, we used the statistical program GoldVarbX (SANKOFF; TRAGLIAMONTE and SMITH, 2006). To perform this study, it was necessary to recruit a number of 10 respondents residents in São Paulo for at least two years. The present data collection followed the styles of interview and ethnographic observation, the latter being only possible style with four speakers of this study. Finally, to form the proposed discussion that makes up the corpus, the research is based on theoretical pillars that complement theoretically each other: the Language Variation Theory developed by Labov, (1966; 1972; 1983); Labov et al., 2006 [1968]; Labov, 2008 [1972]); The Communication Acommodation Theory (GILES et al., 1973; GILES, 1977; GILES et al., 2010 [1991]) and some considerations on language attitudes (LAMBERT, 1967; GILES et al., 2010 [1991] ) and COUPLAND (2007).